2008
DOI: 10.1155/2008/343714
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Films for Self‐Detection and Decontamination

Abstract: Methods that rapidly detect, characterize, quantify, and decontaminate surfaces are essential following chemical or biological incidents. Our work focused on developing a "smart" surface, one that monitors itself and the overlying atmosphere and triggers a decontamination step when surface contamination is detected. Titanium dioxide was used to coat a ceramic surface containing skeletal impregnated platinum electrodes. The electrical resistance of the surface became altered by the introduction of a contaminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…TiO 2 is one of the most commonly used photocatalysts, with anatase (E g = 3.23 eV) and rutile (E g = 3.02 eV) crystal forms commonly used for this application. It can be activated by near UV illumination (300–370 nm) as well as UV light (254 nm), and it can degrade a broad range of molecules for use in indoor air purification [48], including alkanes, ketones, alcohols, phenols, and aromatic compounds [49]. The photodegradation of formaldehyde results in carbon dioxide [50]: TiO2true⟶hνe-+h+H2OH++OH-h++OH-OHe-+O2O2-HCHO+OHHCO+H2OHCO+OHHCOOHHCOOH+2h+CO2+2H+…”
Section: Microscale Formaldehyde Sensorsmentioning
confidence: 99%
“…TiO 2 is one of the most commonly used photocatalysts, with anatase (E g = 3.23 eV) and rutile (E g = 3.02 eV) crystal forms commonly used for this application. It can be activated by near UV illumination (300–370 nm) as well as UV light (254 nm), and it can degrade a broad range of molecules for use in indoor air purification [48], including alkanes, ketones, alcohols, phenols, and aromatic compounds [49]. The photodegradation of formaldehyde results in carbon dioxide [50]: TiO2true⟶hνe-+h+H2OH++OH-h++OH-OHe-+O2O2-HCHO+OHHCO+H2OHCO+OHHCOOHHCOOH+2h+CO2+2H+…”
Section: Microscale Formaldehyde Sensorsmentioning
confidence: 99%
“…Within the past decades TiO 2 thin films have found a large number of interesting applications in catalysis 1–4, anti‐reflection interference filters 5, solar cells 6–9, rechargeable batteries 10, photo‐decomposition of environmental pollutants 11–14, biomedical application 15, capacitors 16, 17, optical waveguides 18, electrochromic applications 19, and smart windows 20. More recently, titania was found to exhibit chemoresistive properties, i.e., it was found that it can sense gases at moderate temperatures (200–400 °C) and the sensing properties have been presented in a large number of publications over the years 21–25.…”
Section: Introductionmentioning
confidence: 99%